The Application of SWOT-analysis in the Formulation of Income Growth Strategies of Greek Rural Households - Sdrolias, Labros; Bitzenis, Aristidis; Semos, Anastasios; Kontakos, Panagiotis; Mattas, Konstadinos; Tsikaridou, Efthymia; Škodová Parmová, Dagmar (University of Macedonia, 2017)
As a consequence of the major changes in recent years in the international environment of the agricultural market, combined with the phenomenon of severe economic crisis in our country, rural households seem unprepared to cope with these new conditions, resulting in their income being insufficient for a decent living. High unemployment, on the other hand, greatly complicates the search for complementary or even alternative forms of employment, which could at least contribute to partially mitigating this situation. Therefore, it is vital that a series of specialized scientific techniques and processes be established as soon as possible, aimed at the search for a new "road map" that will contribute effectively to the investigation of all parameters of rural households’ environment, which are responsible for this long-running condition. Also, it will highlight and indicate any kind of possibilities and opportunities, which may result in a continued strengthening of the financial position of these households. The use of one of the basic tools of strategic management, i.e. the SWOT-Analysis, can in the best and more colorful way, contribute to the achievement of this objective.
Keywords: Rural Households; Income Enlargement; Multiple Employment; SWOT-Analysis; Development Strategies; Greece